2019
DOI: 10.3390/ma12101615
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Cyclic Void Growth Model for Ultra-Low Cycle Fatigue Prediction of Steel Bridge Piers

Abstract: The cyclic void growth model (CVGM) is a micro-mechanical fracture model that has been used to assess ultra-low cycle fatigue (ULCF) of steel structures in recent years. However, owing to the stress triaxiality range and contingency of experimental results, low goodness of fit is sometimes obtained when calibrating the model damage degradation parameter, resulting in poor prediction. In order to improve the prediction accuracy of the CVGM model, a model parameter calibration method is proposed. In the research… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…In Equations (4)–(6), T is the stress triaxiality, is the cumulative equivalent plastic strain at the beginning of each tension cycle, and are the increment of equivalent plastic strain at each tension and compression cycle, respectively, λ is the damage degradation parameter of materials, and η is the fracture parameter under monotone loading. This paper adopts the CVGM fracture criterion calibrated by Li [ 34 ] to calculate the ULCF crack-initiation life of corroded steel piers at the corner of the weld toe. The criterion divides different applications of the damage degradation parameter by the average stress triaxiality.…”
Section: Structural Parameters and Ulcf Failure Simulationmentioning
confidence: 99%
“…In Equations (4)–(6), T is the stress triaxiality, is the cumulative equivalent plastic strain at the beginning of each tension cycle, and are the increment of equivalent plastic strain at each tension and compression cycle, respectively, λ is the damage degradation parameter of materials, and η is the fracture parameter under monotone loading. This paper adopts the CVGM fracture criterion calibrated by Li [ 34 ] to calculate the ULCF crack-initiation life of corroded steel piers at the corner of the weld toe. The criterion divides different applications of the damage degradation parameter by the average stress triaxiality.…”
Section: Structural Parameters and Ulcf Failure Simulationmentioning
confidence: 99%
“…In order to facilitate the application of the proposed CVGM in engineering practice, Liao et al [ 27 , 28 ] and Yin et al [ 29 ] calibrated the parameters in the micro-mechanism model for the commonly used structural steels by experiments. Li et al [ 30 ] found that the level of the stress triaxiality has a significant impact on the damage degradation parameter, and a modified calibration method was proposed in their study. These research findings and proposed methods can be used to evaluate the fatigue failure caused by LCF loadings without considering the HCF pre-damages, namely these studies focused on the LCF properties of the damage free materials.…”
Section: Introductionmentioning
confidence: 99%
“…To facilitate the application of the micromechanical model, Liao et al [19][20] and Yin et al [21] calibrated the parameters in the CVGM by material tests and scanning electron microscope tests. Li et al [22] proposed a new CVGM parameter calibration method to extend the scope of its application to a relatively lower-stress triaxiality condition. Moreover, the effect of the damage degradation parameter on the prediction of ULCF failure in steel bridge piers was discussed by them.…”
Section: Introductionmentioning
confidence: 99%